Plastik Ramah Lingkungan - Rully Masriatini; Muhrinsyah Fatimura; Muhammad Bakrie; Aan Sefentry; Reno Firiyanti; husnah husnah; Nurlela Nurlela; Agus Wahyudi (Unika Santu Paulus Ruteng, 2023)
The problem of plastic waste based on petroleum becomes a serious problem. The existence of plastic waste used as wrapping food for snacks and other uses causes pollution in the soil, air and water. To overcome this, Chemical Engineering Study Program at PGRI Palembang University introduced and made biodegradable plastic based on starch to students at SMK Negeri I Prabumulih as an alternative to conventional plastics based on petroleum. The implementation of the activity is carried out by presenting the subject and making the biodegradable plastic. This biodegradable plastic is the results of research that is applied in the form of community service and it is expected to open people's minds in reducing and utilizing plastic waste